An esophageal stent integrated with wireless battery-free movable photodynamic-therapy unit for targeted tumor treatment - Qian Han; Pingjin Zou; Xianhao Wei; Junyang Chen; Xiaojiao Li; Li Quan; Ranlin Wang; Lili Xing; Xinyu Xue; Yi Zhou; Meihua Chen (Materials Today Bio)
Esophageal cancer is the eighth most common cancer worldwide and the sixth leading cause of cancer-related deaths. In this study, we propose a novel esophageal stent equipped with a wireless, battery-free, and movable photodynamic therapy (PDT) unit designed to treat esophageal tumors with flexibility, precision, and real-time control. This system integrates a PDT unit and an electrochemical pneumatic soft actuator into a conventional esophageal stent. Each module incorporates a piezoelectric transducer capable of receiving external ultrasound to power the respective module. These transducers selectively respond to different external ultrasound frequencies, enabling independent operation without mutual interference. The therapy module provides a light source for PDT, inducing the production of cytotoxic reactive oxygen species (ROS) in tumor cells and promoting apoptosis. The pneumatic actuator based on electrochemical principles plays a critical role in controlling the position of the PDT light source, enabling the movement of the therapy module up to 200 mm within 15 min. This allows real-time control to maintain the light source near the tumor, ensuring precise and targeted treatment. The system can wirelessly and in real-time control the PDT light source's position via external ultrasound, offering a novel approach for treating esophageal cancer patients according to the need of tumor's progression.